Unveiling Pre-Service Teachers’ Attitudes Toward Teaching: The Role of Pedagogical Practicums (2016)
This article reports a research developed at Universidad Pedagógica y Tecnológica de Colombia with a group of pre-service teachers that was immersed in an English teaching practicum. The main purpose of this inquiry was to find out the role that practicum exerted on novice teachers’ attitudes towards teaching. Data were collected through interviews, questionnaires, verbal reports, and artifacts. The results evidenced the English practicum provided the teachers being trained opportunities to consider what teaching entails. Thus, the participants were able to reflect, develop awareness, positive attitudes, and satisfaction towards their teaching practice.